Highly Sensitive and Selective Detection of Steroid Hormones Using Terahertz Molecule-Specific Sensors - Lee, Sang-Hun; Lee, Donggeun; Choi, Man Ho; Son, Joo-Hiuk; Seo, Minah (AMER CHEMICAL SOC, 2019)
Discrimination and quantification of trace amounts of steroid hormones in biological specimens are needed to elucidate their changing expression because their biological functions are responsible for the development and prevention of endocrine disorders. Although mass-spectrometry-based assays are most commonly recommended, development of a new type of highly sensitive and selective detection methods in clinical practices is needed. Here, we introduce a label-free type of terahertz molecule sensor capable of sensing and identifying progesterone and 17 alpha-OH-progesterone selectively. Nanoslot-array-based sensing chips were used as launching pads for absorption cross-section enhancement of molecules at a reliable terahertz frequency. With use of nanoslots with resonances at 1.17 THz corresponding to intrinsic THz absorption resonance mode for progesterone and at 1.51 THz for 17 alpha-OH-progesterone, respectively, each steroid shows prominent transmittance change in terms of its amount. In particular, the sensing performance has been much improved by controlling evaporation speed, in turn resulting in an efficient, homogeneous distribution of the molecules onto a sensing hot spot.
Keywords: TIME-DOMAIN; LABEL-FREE; METAMATERIAL; SPECTROSCOPY; SERUM